Kemampuan Mengidentifikasi Informasi dalam Surat Dinas pada Siswa Kelas VII SMP Negeri 7 OKU - Sanjaya, Muhamad Doni; Sanjaya, Muhamad Rama; Sandra, Dera Okta (STKIP PGRI Bandar Lampung, 2020)
This study aims to determine the ability of grade VII students of SMP Negeri 7 OKU to identify information in official letters, as well as to determine the difficulties of students in identifying information in official letters. This research is a descriptive research type. The population was all class VII students of SMP Negeri 7 OKU, amounting to one class, namely 78 students, the sample was 30 students. Data collection techniques are test, questionnaire and interview techniques. Based on the test results, it can be seen that 29 students (96.7%) can be categorized as capable and there is 1 student (3.33%) who can be categorized as incapable. Furthermore, the 9 students were given a questionnaire to find out about the learning difficulties they experienced and the results showed that students did not like learning to identify information in official letters because students were less able to remember or reveal about identifying information in official letters because most students never identified the information in the letter. offices and students will only read because of demands or assignments from the teacher. Based on the interview analysis, students are interested in learning to identify information in official letters and for students who have not been able to be given the task to understand again. It can be seen that there are some students who have not reached the specified KKM, namely 9 students, and are given additional assignments to better understand the material regarding identifying information in official letters such as assignments to make official letters or looking for examples of official letters. Thus, it can be concluded that grade VII students of SMP Negeri 7 OKU are categorized as capable of identifying information in the official letter.